Respuesta :

frika

Answer:

See explanation

Step-by-step explanation:

1 step:

n=1, then

[tex]\sum \limits_{j=1}^1 2^j=2^1=2\\ \\2(2^1-1)=2(2-1)=2\cdot 1=2[/tex]

So, for j=1 this statement is true

2 step:

Assume that for n=k the following statement is true

[tex]\sum \limits_{j=1}^k2^j=2(2^k-1)[/tex]

3 step:

Check for n=k+1 whether the statement

[tex]\sum \limits_{j=1}^{k+1}2^j=2(2^{k+1}-1)[/tex]

is true.

Start with the left side:

[tex]\sum \limits _{j=1}^{k+1}2^j=\sum \limits _{j=1}^k2^j+2^{k+1}\ \ (\ast)[/tex]

According to the 2nd step,

[tex]\sum \limits_{j=1}^k2^j=2(2^k-1)[/tex]

Substitute it into the [tex]\ast[/tex]

[tex]\sum \limits _{j=1}^{k+1}2^j=\sum \limits _{j=1}^k2^j+2^{k+1}=2(2^k-1)+2^{k+1}=2^{k+1}-2+2^{k+1}=2\cdot 2^{k+1}-2=2^{k+2}-2=2(2^{k+1}-1)[/tex]

So, you have proved the initial statement

ACCESS MORE